2019
DOI: 10.1186/s12895-019-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of a dimeticone-based pediculicide following a brief application: in vitro assays and randomized controlled investigator-blinded clinical trial

Abstract: BackgroundIncreasing resistance of head lice against neurotoxic agents and safety concerns have led to the search for treatment alternatives. Dimeticones with a physical mode of action are safe, and bear a reduced risk for the development of resistance.MethodsWe performed in vitro bioassays to assess pediculicidal and ovicidal activities of a new dimeticone-based product, and a randomized controlled clinical trial to assess efficacy, following 10 min application. Of 153 individuals screened, 100 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…This carefully designed combination of dimethicones of different molecular weights together with high concentration of squalane and a small amount of lauryl alcohol improves its mortality potency and confers good cosmeticity. Its good efficacy is similar to the data reported in other studies of different silicone-based commercial pediculicides (Gallardo et al 2012 ; Heukelbach et al 2019 ). Furthermore, the formulation shows full efficacy in only 2 min, following the global tendency to reduce the application time in order to increase treatment compliance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This carefully designed combination of dimethicones of different molecular weights together with high concentration of squalane and a small amount of lauryl alcohol improves its mortality potency and confers good cosmeticity. Its good efficacy is similar to the data reported in other studies of different silicone-based commercial pediculicides (Gallardo et al 2012 ; Heukelbach et al 2019 ). Furthermore, the formulation shows full efficacy in only 2 min, following the global tendency to reduce the application time in order to increase treatment compliance.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the formulation shows full efficacy in only 2 min, following the global tendency to reduce the application time in order to increase treatment compliance. Other in vitro studies of physical acting agents confirm that motile head lice and eggs can be killed within a few minutes, although not all formulations achieve 100% ovicidal activity (Abdel-Ghaffar et al 2012 ; Abdel-Ghaffar et al 2010 ; Gallardo et al 2012 ; Heukelbach et al 2019 ; Mehlhorn et al 2011 ; Oliveira et al 2007 ; Strycharz et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, teaching the way of using pediculicides properly and health tips were effective in treating and reducing recurrence. Several studies have been conducted in the treatment of head lice infestation [ 18 19 ]. Most studies have compared different treatments [ 19 21 ], and several studies have been conducted on the effectiveness of training programs on preventing pediculosis capitis [ 22 – 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heukelbach et al . [ 42 ] indicated that the efficacy of dimethicone for treating lice was 98%. kdr -type gene mutations cause the poor efficacy of permethrin.…”
Section: Discussionmentioning
confidence: 99%